Two-Component Systems Are Involved in the Regulation of Botulinum Neurotoxin Synthesis in Clostridium botulinum Type A Strain Hall - Connan, Chloé; Brueggemann, Holger; Mazuet, Christelle; Raffestin, Stéphanie; Cayet, Nadège; Popoff, Michel R. (PLOS ONE, 2012)
Clostridium botulinum synthesizes a potent neurotoxin (BoNT) which associates with non-toxic proteins (ANTPs) to form complexes of various sizes. The bont and antp genes are clustered in two operons. In C. botulinum type A, bont/A and antp genes are expressed during the end of the exponential growth phase and the beginning of the stationary phase under the control of an alternative sigma factor encoded by botR/A, which is located between the two operons. In the genome of C. botulinum type A strain Hall, 30 gene pairs predicted to encode two-component systems (TCSs) and 9 orphan regulatory genes have been identified. Therefore, 34 Hall isogenic antisense strains on predicted regulatory genes (29 TCSs and 5 orphan regulatory genes) have been obtained by a mRNA antisense procedure. Two TCS isogenic antisense strains showed more rapid growth kinetics and reduced BoNT/A production than the control strain, as well as increased bacterial lysis and impairment of the bacterial cell wall structure. Three other TCS isogenic antisense strains induced a low level of BoNT/A and ANTP production. Interestingly, reduced expression of bont/A and antp genes was shown to be independent of botR/A. These results indicate that BoNT/A synthesis is under the control of a complex network of regulation including directly at least three TCSs.